Implications of recent earthquakes on seismic risk : (Imperial College Press, 2000)
Papers presented at the Japan-UK Seismic Risk Forum, Third Workshop, April 6-7, 2000, Imperial College, London, UK. Discusses important lessons drawn from recent earthquakes, in particular the Kobe earthquake of 1995 and the earthquakes in Turkey and Greece in 1999.